2013
DOI: 10.1155/2013/785835
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, Leptin, and Resistin in Asthma: Basic Mechanisms through Population Studies

Abstract: Adipokines, factors produced by adipose tissue, may be proinflammatory (such as leptin and resistin) or anti-inflammatory (such as adiponectin). Effects of these adipokines on the lungs have the potential to evoke or exacerbate asthma. This review summarizes basic mechanistic data through population-based and clinical studies addressing the potential role of adipokines in asthma. Augmenting circulating concentrations of adiponectin attenuates allergic airway inflammation and airway hyperresponsiveness in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
1
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 120 publications
(234 reference statements)
3
106
1
15
Order By: Relevance
“…It seems that the association between obesity and asthma is complex and multifaceted and is likely explained by many mechanisms. Recently, a distinctive role is suggested for leptin in the prognosis of asthma in patients with obesity and also a link between leptin and asthma is suggested by some studies (3,16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the association between obesity and asthma is complex and multifaceted and is likely explained by many mechanisms. Recently, a distinctive role is suggested for leptin in the prognosis of asthma in patients with obesity and also a link between leptin and asthma is suggested by some studies (3,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that during the development of obesity, hypertrophy of the adipose tissue results in local tissue hypoxia, adipocyte necrosis, and macrophage recruitment. These factors, in association with each other, lead to toll-like receptor signaling via fatty acids, and subsequently, result in the gen- Leptin is a 16-kD protein derived from the obese gene and is expressed predominantly in adipocytes (16). It is considered that many factors affecting the serum leptin level including gender, age, puberty, BMI, breast feeding, and steroid therapy (12,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of clarity, the endocrine regulation of the lung immune system is not addressed in detail in the present review. Readers are referred to recent reviews that are covering this particular topic (Townsend et al 2012a, Wright 2012, Sood & Shore 2013.…”
Section: Mediators Released By Remote Organs On Asm Contractionmentioning
confidence: 99%
“…Leptin rather acts through the central nervous system to attenuate the constitutive muscarinic activation of ASM that emanates from the parasympathetic inputs of the vagi However, the effect of leptin in the context of asthma is not clear. This subject has been reviewed recently (Sood & Shore 2013). The level of leptin in the blood and adipose tissue is generally elevated in asthmatics.…”
Section: Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation